LEARNING OBJECTIVES OF NEUROANATOMY FOR UNDERGRADUATE MEDICINE: A DELPHI PROCESS - Gabriela Claudia; Siti Munawaroh; Nanang Wiyono; Yunia Hastami (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Anatomy is a basic science needed by clinicians in order to perform medical procedures safely and effectively. Nowadays, the amount of time available for teaching anatomy is reduced because of the introduction of new subjects to medical program.  Whereas, the anatomy itself is already too complex to learn, especially neuroanatomy. As the result, medical students tend to find difficulties in mastering anatomy. In fact, inadequate understanding of anatomy has an impact to medical errors. The aim of this study is to compose neuroanatomy learning objectives based on consensus of anatomy lecturers in Indonesia.Methods: Two-rounds Delphi process was employed in this qualitative study. Twenty anatomy lecturers from all over Indonesia were recruited as panels based on purposive sampling technique. Panels of first round of Delphi were requested to compose learning objectives based on neuroanatomy core syllabus available in the questionnaire. They had to list each learning objective with cognitive level according to Bloom’s taxonomy. In the second round, panels were asked to score each learning objectives based on their level of importance  from 1 to 4. Learning objectives scored 3 or 4 by 60% panels were qualified as the final results. Results: 66 learning objectives were obtained in the first round of Delphi and became 68 due to modification process conducted by expert. In the second round, 67 learning objective were achieved, and became 52 after final process of expert modification. The learning objectives cognitive level varied in C1-C3 according to Bloom’s Taxonomy.Conclusion: This study obtained 52 learning objectives of neuroanatomy.